Case Report: Rehabilitation assessment and exercise using cardiopulmonary exercise test after coronavirus-disease pneumonia - Kouda, Ken; Konishi, Hideki; Kubo, Toshikazu; Tajima, Fumihiro (Frontiers in Rehabilitation Sciences, 2025)
Coronavirus disease (COVID-19) affects not only respiratory function, but also physical function and decreases activities of daily living. Cardiopulmonary evaluation using cardiopulmonary exercise test (CPET) was performed in two patients with persistent respiratory distress one month after acute treatment for COVID-19. The results showed decrease in exercise tolerance, ventilation ability, oxygenation ability, heart rate reserve, stroke volume, and muscle metabolism in both cases. By performing rehabilitation exercise according to the results of CPET, both patients were able to withdraw from oxygen inhalation, improve their functions (17.4 vs. 22.1 in case 1 and 9.0 vs. 16.1 in case 2 on peak exercise aerobic capacity), and were discharged to their homes three months after training. Rehabilitation assessment and exercise using CPET in COVID-19 patients could be safe and useful.